Site selection of photovoltaic power plants in a value chain based on grey cumulative prospect theory for sustainability: A case study in Northwest China. (1st April 2017) - Liu, Jicheng; Xu, Fangqiu; Lin, Shuaishuai
Abstract: Installing a photovoltaic (PV) power plant at a proper location has been a critical problem for the system planners and investors. In this study, grey cumulative prospect theory is employed to study the site selection of PV power plants from the perspective of sustainability. First, considering the sustainable development, eight decision-making criteria are identified and divided into three categories: geographical conditions, economic profits and environmental benefits. The decision-making steps of grey cumulative prospect theory are then proposed to select the optimal alternative and in this method, an optimization model is used to obtain the importance of criteria. The proposed method has also been implemented in a case of four cities in Northwest China in which the optimal alternative, Yulin city, is selected with the highest prospect value. Finally, a comparison analysis of multi-criteria decision-making methods and a sensitivity analysis of all criteria are performed and the results show that the proposed method can be used effectively for the site selection of PV power plants. Highlights: The criteria system of site selection of PV power plants was built from the perspective of sustainability. The grey cumulative prospect theory was employed to determine the optimal location for PV power plants. A case in Northwest China was studied to select the optimal city to build a PV power plant. A comparison analysis and a sensitivity analysis were performed to verify the robustness of the decision result.